The Significance of Human Resource Management in Enhancing Employee Performance from An Islamic Standpoint - Widyatmoko, Fahri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The primary function of management in an organization is to oversee and control the organizational structure according to the company's objectives. It involves supporting managers in their supervision and selection of personnel, facilitating efficient decision-making processes, and ensuring overall organizational orderliness. Nevertheless, the progress in developing the function of human resources is hindered by the insufficient ability of human resources to quickly adapt to technology. The objective of this essay is to determine the methodology of discovering The significance of Human Resource Management in enhancing employee performance from an Islamic standpoint. The research was conducted in a descriptive manner, utilizing literature studies and discussing the findings of earlier research. The findings of this study highlight that the objective of human resource management is to mitigate a range of unwanted outcomes, including the recruitment of unsuitable candidates, excessive employee turnover, suboptimal work performance, unproductive interviews, and other related issues. Another issue that negatively impacts the organization is that human resource management promotes a religious ideology that centers around Islamic beliefs. This implies that the objective of human resource management should be to align with the purpose of human existence, which is to consistently acknowledge and incorporate God in all aspects of one's life.